Perancangan Desain Antarmuka Website Monitoring Data SUTM pada PT. PLN UP3 Lubuk Pakam Menggunakan Metode Design Thinking - Aulia Ramadhani Lubis; Heri Santoso (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This research aims to develop a website interface that allows the monitoring of Medium Voltage Air Channel Data (SUTM) at PT PLN UP3 Lubuk Pakam with the hope of improving the effectiveness of direct power network monitoring. The methodology applied is design thinking, which consists of five steps: empathize, define, ideate, prototype, and test. To understand user needs, direct observations were made in the field, which were then analyzed descriptively-qualitatively, and the results of the analysis are presented in the form of diagrams such as flowcharts and use cases. This interface is designed using Figma and results in a prototype that is based on a Single Page Application (SPA) with several main pages, including: Dashboard, Network Map, Data Monitoring, Disturbance and Inspection Reports, Inspection History, and Login modal.. Each page is designed to display technical data such as current, voltage, cable temperature, and infrastructure status through interactive Chart.js graphs as well as map visualizations that utilize the Google Maps API. The system also features the ability to export data in Excel or PDF format for reporting purposes. Evaluation is conducted with unit tests on each interface page that include clarity of view, filter interactivity, navigation speed, and export functionality. Testing results show that all units operate as expected by users. This interface is rated as responsive, informative, and user-friendly. A prototype has also been prepared to be integrated with an IoT-based backend and real-time database system. It is expected that this design can improve efficiency in monitoring and technical decision-making, as well as serve as an example for the development of similar systems in other PLN units to strengthen the reliability of electricity distribution at the national level.